If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -27 = 45 + 11x Reorder the terms: -27 + 7x = 45 + 11x Solving -27 + 7x = 45 + 11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11x' to each side of the equation. -27 + 7x + -11x = 45 + 11x + -11x Combine like terms: 7x + -11x = -4x -27 + -4x = 45 + 11x + -11x Combine like terms: 11x + -11x = 0 -27 + -4x = 45 + 0 -27 + -4x = 45 Add '27' to each side of the equation. -27 + 27 + -4x = 45 + 27 Combine like terms: -27 + 27 = 0 0 + -4x = 45 + 27 -4x = 45 + 27 Combine like terms: 45 + 27 = 72 -4x = 72 Divide each side by '-4'. x = -18 Simplifying x = -18
| 325=6+7 | | 2a+6+4a+13= | | x^2+x-6=9-x | | 3x^(3/4)=-24 | | 2t^2-7t-5=0 | | 27/S=9 | | -X^2-11x-25=0 | | 4+3=7y-21 | | 1.5a=1.6a+5 | | 22-3x=-8 | | 2=t/-14 | | 1.25x=8 | | 4r=3(r-2) | | 94=8j+30 | | y=4(x+6)-7 | | x-5/9=8/9 | | 5+4x+5+48= | | -3(t-4)+9t=8t-6 | | 60y^2+3y-36=0 | | x^2=14-7x | | 5(x-8)+26= | | 5x-4(4x-1)=2 | | -6x-142=2x+98 | | 5x+45+9x=180 | | 17=64-n | | i7n/9-62=5n/9-49 | | 31x=56 | | Y/3-4=-2 | | B/5-2=2 | | 4+-6+9=x | | .10x+12y=2990 | | a/4-b/3=5/12 |